Recycling used coffee grounds as fine aggregate in alkali-activated lightweight non-load-bearing composites - Quoc Dung Huynh; Hoang Nhat Huy Luong; Nhat Tan Ngo; Thanh Hau Duong; Thanh Binh Nguyen; Tri Khang Lam; Trong Phuoc Huynh (CTU Journal of Innovation and Sustainable Development)
Coffee is one of the most consumed drinks, which releases large amounts of used coffee grounds (UCG), causing environmental problems. Thus, UCG was re-used in combination with bottom ash (BA) as fine aggregates in making alkali-activated non-load-bearing lightweight composites (ANLC) in this study. To evaluate the effect of UCG on the properties of ANLC, seven ANLC mixtures with UCG/BA ratios of 0/100, 5/95, 10/90, 15/85, 20/80, 25/75, and 30/70 were prepared. Results showed that the properties of ANLC were influenced significantly by UCG contents. Indeed, an increase in UCG content led to a decrease in dry density, strength, and drying shrinkage while increasing the ANLC’s water absorption, except for the specimen with 5% UCG incorporation. Correlations among properties of ANLC were established and the potential applications of ANLC in real practice were also suggested, proving that the ANLC could be applied to non-load-bearing elements. Among the mixtures, the 28-day ANLC specimen containing 5% UCG exhibited the highest flexural and compressive strengths of 7.12 MPa and 39.4 MPa, respectively, and the lowest water absorption of 10.29% with the relatively low dry density of 1671 kg/m3, indicating the feasibility of using UCG as fine aggregate in the production and application of ANLC.